The Effectiveness of Wordwall Media in Enhancing Students' Writing Skills in Descriptive Texts at Senior High School Bandar Lampung Through Task-Based Language Teaching - Qonita Vidina; Achmad Yudi Wahyudin (Universitas Islam Negeri Palopo, 2025)
This study investigated the effectiveness of integrating Wordwall media with Task-Based Language Teaching (TBLT) to improve eleventh-grade students’ descriptive writing skills at SMAN 14 Bandar Lampung. A quasi-experimental one-group pre-test and post-test design was employed with 36 students. Writing scores were assessed using a modified rubric covering content, organization, vocabulary, language use, and mechanics. Inter-rater reliability was excellent (pre-test r = .985; post-test r = .998, p < .01), and normality tests confirmed parametric assumptions. The results showed significant improvement in students’ writing performance after the intervention (pre-test mean = 54.83; post-test mean = 76.42; paired-samples t-test, t = 14.85, df = 35, p < .001), with the largest gains in organization and language use. Qualitative interviews with high, medium, and low achievers revealed increased motivation, engagement, and peer-supported learning. These findings suggest that integrating gamified digital platforms like Wordwall within a task-based framework effectively enhances descriptive writing skills in EFL classrooms.